Thin films and coatings : toughening and toughness characterization - Zhang, Sam (Advances in materials science and engineering., 2016)
Thin Films and Coatings: Toughening and Toughness Characterization captures the latest developments in the toughening of hard coatings and in the measurement of the toughness of thin films and coatings. Featuring chapters contributed by experts from Australia, China, Czech Republic, Poland, Singapore, Spain, and the United Kingdom, this first-of-its-kind book:Presents the current status of hard-yet-tough ceramic coatingsReviews various toughness evaluation methods for films and hard coatingsExplores the toughness and toughening mechanisms of porous thin films and laser-treated surfacesExamines.